Speak up! Barriers to challenging erroneous decisions of seniors in anaesthesia. (November 2016) - Beament, T.; Mercer, S. J.
Summary: 'Speaking up' or the ability to effectively challenge erroneous decisions is essential to preventing harm. This mixed‐methods study in two parts explores the concept of 'barriers to challenging seniors' for anaesthetic trainees, and proposes a conceptual framework. Using a fully immersive simulation scenario with unanticipated airway difficulty, we investigated how junior anaesthetists (one to two years of training) challenged a scripted error. We also conducted focus groups with senior trainees (three to seven years of training) and undertook a 'thematic network analysis' of responses. Junior anaesthetic trainees challenged erroneous decisions effectively, but trainees with an additional year of experience challenged more quickly and effectively, combining 'crisp‐advocacy‐inquiry challenge' with 'non‐verbal cues'. Focus group analysis conceptualised a 'barrier network' with three main themes: concerns around relationships; decision‐making; and risk/cost–benefit. Emotional maturity is an important protective layer around decisions to challenge. Despite significant multifactorial barriers, systematic training in effective 'speaking up' could improve the confidence and ability of juniors to challenge erroneous decisions.